Learning in foreign cultures : self-reports learning effectiveness across different instructional techniques - Rajaram, Kumaran (2014)
Substantial numbers of Chinese mainland students are enrolled in overseas Western-based business courses but are dislocated from their home cultures. Business education curriculum and course designers need to understand how these students are best trained in western style education programs. Four-hundred students in Singaporean business training programs provided differential ratings of perceived learning effectiveness, plus dislocation measures of familiarity, comfort and ease of knowledge transfer for each of ten commonly used instructional strategies previously investigated by Rodrigues, four of which he termed “active” and six “passive”. In terms of perceived learning effectiveness alone, Mainland Chinese students reported clear differences. In order of decreasing effectiveness, they reported lectures by instructors, case-studies, group projects, videos, guest speakers, classroom presentations,individual research projects, classroom discussions, computerized learning and lastly, reading textbooks. The study presents strategies and practices for facilitating effective learning for mainland Chinese students in western based education – choice of instructional techniques and mixtures, attention to students’ cultural dislocation, comfort,familiarity, and ease of knowledge transfer.